Plataformas digitales y la ética en el ejercicio periodístico - Goya García, Danna Aracely (2024)
In this work, the analysis of the right to reply in digital media in comparison to traditional media was carried out. The procedure followed by the media outlets La Posta and El Universo in obtaining and contrasting information, diversification of sources and compliance with ethical principles and deontological standards is investigated. These standards contribute to strengthening responsibility and truthfulness in the exercise of journalism. Ethics refers to the values and principles that a media and journalist must follow, these are: honesty, diversity, independence, commitment to the public interest and the protection of confidential sources. Professionals claim that these values and principles help maintain their credibility and public trust..........